Microenvironment-confined kinetic elucidation and implementation of a DNA nano-phage with a shielded internal computing layer - Decui Tang; Shuoyao He; Yani Yang; Yuqi Zeng; Mengyi Xiong; Ding Ding; Weijun Wei; Yifan Lyu; Xiao-Bing Zhang; Weihong Tan (Nature Communications)
Abstract Multiple receptor analysis-based DNA molecular computation has been developed to mitigate the off-target effect caused by nonspecific expression of cell membrane receptors. However, it is quite difficult to involve nanobodies into molecular computation with programmed recognition order because of the “always-on” response mode and the inconvenient molecular programming. Here we propose a spatial segregation-based molecular computing strategy with a shielded internal computing layer termed DNA nano-phage (DNP) to program nanobody into DNA molecular computation and build a series of kinetic models to elucidate the mechanism of microenvironment-confinement. We explain the contradiction between fast molecular diffusion and effective DNA computation using a “diffusion trap” theory and comprehensively overcome the kinetic bottleneck of DNP by determining the rate-limiting step. We predict and verify that identifying trace amount of target cells in complex cell mixtures is an intrinsic merit of microenvironment-confined DNA computation. Finally, we show that DNP can efficiently work in complex human blood samples by shielding the interference of erythrocytes and enhance phagocytosis of macrophages toward target cells by blocking CD47-SIRPα pathway.